Antimicrobial Stewardship: uma contribuição baseada na espectroscopia Raman amplificada por superfície - SERS - Marangoni, Caroline Guimarães Pançardes da Silva (2022)
The discovery of penicillin in 1928 was considered one of the most critical advances in the history of medicine, because only with the use of antimicrobials was it possible to treat infections previously incurable. However, over time, microorganisms have developed resistance mechanisms to these drugs, due to indiscriminate use. The emergence of multi-resistant bacteria (MDR), the harmful bacteria, is considered a severe public health problem that, according to WHO forecasts, could lead to 10 million deaths/year by 2050. The challenge of developing new antimicrobials brings with it the need to verify the effectiveness of the existing ones, as well as a better understanding of the mechanisms of resistance, hence the importance of developing fast and lowcost techniques for monitoring the action of antibiotics. Here we present an alternative based on nanophotonics that consists of the use of surface-enhanced Raman spectroscopy (SERS) mediated by different nanoparticles, for the detection of antimicrobials, with emphasis on some β-lactam antibiotics commonly prescribed in critically ill patients. The experiments proved the possibility of identifying spectra with characteristic vibrations (fingerprints) of these antimicrobials, via SERS, with the evidence that this technology is a great contributor to the Antimicrobial Stewardship program, because it makes it possible to identify unique molecules and also the degradation of the antibiotic.